2015
DOI: 10.1002/nav.21638
|View full text |Cite
|
Sign up to set email alerts
|

Optimal replacement of continuously degrading systems in partially observed environments

Abstract: Motivated by wind energy applications, we consider the problem of optimally replacing a stochastically degrading component that resides and operates in a partially observable environment. The component's rate of degradation is modulated by the stochastic environment process, and the component fails when it is accumulated degradation first reaches a fixed threshold. Assuming periodic inspection of the component, the objective is to minimize the long‐run average cost per unit time of performing preventive and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the last two decades, several condition‐based maintenance models have been developed for phased‐mission systems (see, e.g., Refs. ). Our work is closely related to that of Refs.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In the last two decades, several condition‐based maintenance models have been developed for phased‐mission systems (see, e.g., Refs. ). Our work is closely related to that of Refs.…”
Section: Literature Reviewmentioning
confidence: 97%
“…They showed that there exists an optimal threshold-type replacement policy for each environment. Considering similar degradation dynamics, Flory et al (2015) extended the work of Ulukus et al (2012) to partially observable environments. Çekyay and Özekici (2012) defined both the mission process and the degradation process as finite-state Markov processes where the generator of the degradation process depends on the phases of the mission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another common choice is to directly model conditioning monitoring data by a stochastic process, e.g., the gamma process, [4], [5], [6]; failure is defined as the process exceeding a (random) threshold. However, in many practical applications, the physical condition of a machine 1 is characterized by a discrete set of states; see, e.g., [7] for road maintenance, [8] for power system management, [9] for production scheduling, and [10] for optimal replacement of wind turbines. Moreover, in many cases we are not permitted exact observations of the state of the machine.…”
Section: Abbreviations and Acronymsmentioning
confidence: 99%
“…Propositions 1 and 2 indicate that value iteration is a promising method for policy optimization. Equations (10) and 11…”
Section: A Value-iteration Algorithmmentioning
confidence: 99%